THE PREHISTORIC ORIGINS OF EUROPEAN ECONOMIC INTEGRATION. Issue 2 (2021) - Grantham, George
Abstract: It appears likely that at its peak the classical economy was almost as large as that of Western Europe during the Industrial Revolution. The following review of the archeological and document evidence indicates that three events occurring in the first half of the first millennium BC trigger the emergence of a specialized and integrated classical economy after 500 BC: (i) growth in demand for silver as a medium of exchange in economies in the Near East; (ii) technical breakthroughs in hull construction and sailing rig in merchant shipping of the late Bronze Age; (iii) perfection of ferrous metallurgy into the European hinterland. This last event raised agricultural productivity to a level capable of supporting the occupational specialization needed to sustain a vigorous trading economy. To these initial causes may be added the diffusion of alphabetic writing. While it did not create opportunities for long-distance trade, the diffusion of writing supplied the means of responding on a scale large enough economically to matter.